Constructing a Measure of Private-pay Nursing Home Days. Issue 5 (May 2018) - Thomas, Kali S.; Silver, Benjamin; Gozalo, Pedro L.; Dosa, David; Grabowski, David C.; Makineni, Rajesh; Mor, Vincent
Abstract : Background: Nursing home (NH) care is financed through multiple sources. Although Medicaid is the predominant payer for NH care, over 20% of residents pay out-of-pocket for their care. Despite this large percentage, an accepted measure of private-pay NH occupancy has not been established and little is known about the types of facilities and the long-term care markets that cater to this population. Objectives: To describe 2 novel measures of private-pay utilization in the NH setting, including the proportion of privately financed residents and resident days, and examine their construct validity. Design: Retrospective descriptive analysis of US NHs in 2007–2009. Measures: We used Medicare claims, Medicare Enrollment records, and the Minimum Data Set to create measures of private-pay resident prevalence and proportion of privately financed NH days. We compared our estimates of private-pay utilization to payer data collected in the NH annual certification survey and evaluated the relationships of our measures with facility characteristics. Results: Our measures of private-pay resident prevalence and private-pay days are highly correlated ( r =0.83, P <0.001 and r =0.83, P <0.001, respectively) with the rate of "other payer" reported in the annual certification survey. We also observed a significantly higher proportion of private-pay residents and days in higher quality facilities. Conclusions: This new methodology provides estimates of private-pay resident prevalence and resident days. These measures were correlated with estimates using other data sources and validated against measures of facility quality. These data set the stage for additional work to examine questions related to NH payment, quality of care, and responses to changes in the long-term care market. Abstract : Supplemental Digital Content is available in the text.